The Organizational Innovativeness Inventory for information and electronic enterprises: Development and Validation - Chuang, Li-Min; ., Wen-Chia Tsai (Journal of Economics and Behavioral Studies, 2014)
The primary purpose of this study is to develop Taiwan localization and suitable inventory for the measuring organizational innovation in information and electronic enterprises. In review of relevant literatures, and with reference to opinions from scholars and practical experience from enterprises, the framework of the inventory would be initially established. Concerning the inventory reliability, Cronbach’s coefficient, item-total correlation and test-retest reliability coefficient have been employed to test the extent of internal consistency and the stability of the inventory. In the construction of validity, Linear Structural Relation was adopted to carry out confirmatory factor analysis. The suitability and fitness of the seven dimensions and 58 questions have been thus verified. As a result, this inventory with adequate validity and reliability can serve as effective instrument for the measurement of organizational innovation in domestic information and electronic enterprises. The developed questionnaire of this study is a method to quantify the organizational innovation. These instrument targets two areas OI and TI evaluation modelâ€“to assess inattentiveness in an organization.